Acute and 3-month effects of microcrystalline hydroxyapatite, calcium citrate and calcium carbonate on serum calcium and markers of bone turnover: a randomised controlled trial in postmenopausal women. Issue 10 (28th November 2014) - Bristow, Sarah M.; Gamble, Greg D.; Stewart, Angela; Horne, Lauren; House, Meaghan E.; Aati, Opetaia; Mihov, Borislav; Horne, Anne M.; Reid, Ian R.
<x content-type="archive" xml:space="preserve">Abstract</x> Ca supplements are used for bone health; however, they have been associated with increased cardiovascular risk, which may relate to their acute effects on serum Ca concentrations. Microcrystalline hydroxyapatite (MCH) could affect serum Ca concentrations less than conventional Ca supplements, but its effects on bone turnover are unclear. In the present study, we compared the acute and 3-month effects of MCH with conventional Ca supplements on concentrations of serum Ca, phosphate, parathyroid hormone and bone turnover markers. We randomised 100 women (mean age 71 years) to 1 g/d of Ca as citrate or carbonate (citrate–carbonate), one of two MCH preparations, or a placebo. Blood was sampled for 8 h after the first dose, and after 3 months of daily supplementation. To determine whether the acute effects changed over time, eight participants assigned to the citrate dose repeated 8 h of blood sampling at 3 months. There were no differences between the citrate and carbonate groups, or between the two MCH groups, so their results were pooled. The citrate–carbonate dose increased ionised and total Ca concentrations for up to 8 h, and this was not diminished after 3 months. MCH increased ionised Ca concentrations less than the citrate–carbonate dose; however, it raised the concentrations of phosphate and the Ca–phosphate product. The citrate–carbonate and MCH doses produced comparable decreases in bone resorption (measured as serum C-telopeptide (CTX)) over 8 h and bone turnover (CTX and procollagen type-I N-terminal propeptide) at 3 months. These findings suggest that Ca preparations, in general, produce repeated sustained increases in serum Ca concentrations after ingestion of each dose and that Ca supplements with smaller effects on serum Ca concentrations may have equivalent efficacy in suppressing bone turnover.